HUBUNGAN HIGIENE SANITASI DENGAN KANDUNGAN BAKTERIOLOGIS PADA MINUMAN YANG DIJUAL DI SEPANJANG PANTAI LOSARI - Mahmud, Inayah; Astuti, Sri Reski (Politeknik Kesehatan Kemenkes Makassar, 2019)
ABSTRACTFood and beverages trading by street vendors in the process of processing often less attention to sanitation hygiene factors who makes potentially the existence of biological contamination causing digestive infections.The purpose of this research is there is a correlation between the sanitation hygiene with the bacteriological contentin sold the beverages at Losari Beach.The type of this research is quantitative research using observational method withapproach cross sectional. The population is 150 traders,and samples used by 50 traders.The results of this research indicate that there is a correlation hygiene of the handler with bacteriological content(p = 0.011 CC = 0.41). There is a correlation of sanitary equipment with bacteriological content (p = 0,00 CC = 0.64). There is a correlation of sanitation beverage processing with existence bacteriological (p = 0,00 CC = 0,665) and a correlation of storage sanitation with bacteriological content (p = 0,00 CC = 0,687) TheThe conclusion in this research is there is a correlation between hygiene of handlers, sanitation equipment, beverage processing sanitation, and sanitary storage materials with existence bacteriological. Suggestion for traders is have to increase the food sanitation hygiene.Keywords: Hygiene Handkerchief, Sanitation Drink, Bacteriological Content.Â